Transição do cuidado de usuários de um serviço de internação cirúrgica para o domicílio: estudo misto - Bandeira, Danieli (2023)
The thesis aimed to evaluate the care transition of users of a public hospital surgical inpatient service to the home and to understand the management of the care transition in Primary Health Care. A mixed method study with a sequential explanatory strategy was developed. The study scenario comprises the 4th Regional Health Coordination of the State of Rio Grande do Sul. In phase I, users over 18 years of age who underwent surgical procedures in orthopedics and traumatology and were discharged home from a public hospital participated in the study. For the collection of quantitative data, a user identification form and the adapted and validated version of the Care Transition Measure were used. The collected data were tabulated in the Excel program and the analysis was performed using the Statistical Package for Social Sciences, version 21.0. Descriptive and inferential statistics were performed, Student's t-test was used when data were parametric, and Mann Whitney U test when data were non-parametric. The variables normality distribution was evaluated using the Kolmogorov-Smirnov test, Cronbach's Alpha was calculated. A significance level of 5% (p<0.05) was considered. In phase II, ten nurses who work in the Nursing Service of the General Surgery Unit of the same hospital and four coordinators of Primary Health Care participated in the study. Semi-structured interviews were carried out and initially transcribed in full. Afterwards, the free ATLAS.ti program version 22.2.4 was used to help organize the qualitative database, using Minayo's operative proposal as an analytical technique. The data collection period was from September 2020 to August 2022. The study was approved by the Comitê de Ética em Pesquisa under CAAE number 30551920.0.0000.5346 and respected the ethical aspects involving research with humans. Results revealed that the quality of the care transition upon discharge from the surgical hospitalization service of orthopedics and traumatology users was well evaluated 75.17 (±12.36), the factor that received the best evaluation was that of preparation for selfmanagement 76,40 (±13,47) and the factor that received the lowest evaluation was assured preferences 72,56 (±12,32). From the perspective of nurses and managers, the care transition for surgical users of orthopedics and traumatology proved to be deficient, indicating challenges for the Health Care Network in the search for effective communication and articulation, in addition to the importance of the nurse's role as coordinator of the care and facilitator of the care transition and revealed strategies and devices that can be used to effect the care transition. The thesis highlighted the importance of nurses in coordinating care and health education actions and highlighted communication and hospital discharge planning as one of the main challenges to be overcome to effect the care transition.